Gender perspective from the legal feminism of Miguelina Acosta - Santos Gomero, Walber Jose (2022)
Gender perspective is an influential approach in the current context; however, regional studies have not delved into its origin and impact in the legal field. For this reason, this research aims to highlight how a clear understanding and delimitation of the phenomenon in question is already visualized within the reflections of Miguelina Aurora Acosta Cárdenas, trial attorney of the twentieth century. Therefore, based on the analysis of her articles «Reacción femenina en 1918» and «La absolución de Victoria Alfaro y el Dr. Federico Pflucker in 1919», I will try to show that the work of this author considers significant contributions such as the consideration of gender perspective or contextual, structural-historical analysis of the female situation when exercising the right to a defense.